Isotopic signature of plutonium accumulated in cryoconite on glaciers worldwide - Lokas E.; Baccolo G.; Cwanek A.; Buda J.; Koltonik K.; Takeuchi N.; Wachniew P.; Clason C.; Zawierucha K.; Beard D. B.; Ambrosini R.; Pittino F.; et al. (Science of The Total Environment, 2024)
Glaciers are recognized as repositories for atmospheric pollutants, however, due to climate change and enhanced melting rates, they are rapidly transitioning from being repositories to secondary sources of such apollutants. Artificial radionuclides are one of the pollutants found on glaciers that efficiently accumulate onto glacier surfaces within cryoconite deposits; a dark, often biogenic sediment. This work provides information about the accumulation, distribution and sources of plutonium (Pu) isotopes in cryoconite samples from glaciers worldwide. Plutonium is an artificial radionuclide spread into the environment in the last decades as a consequence of nuclear test explosions, accidents and nuclear fuel re-processing. Samples collected from 49 glaciers across nine regions of Earth are considered. Activity concentrations of plutonium in cryoconite are orders of magnitude higher than in other environmental matrices typically used for environmental monitoring (e.g. lichens, mosses, soils and sediments), particularly in the Northern Hemisphere. Isotopic ratios indicate that plutonium contamination of cryoconite is dominated by the global signal of stratospheric fallout related to atmospheric nuclear tests. However, specific glaciers in Svalbard reveal a signature compatible with a contribution from the re-entry of the SNAP-9A satellite in 1964, which was equipped with a 238Pu radioisotope thermoelectric generator. Similarly, an excess of 238Pu is observed in cryoconite from the Exploradores Glacier (Chile). This could be associated with the November 1996 crash of the automatic Interplanetary Station “Mars '96” which was carrying a 238Pu thermoelectric generator. This is the first time ever that an isotopic evidence for this event is reported. These findings highlight the role that cryoconite can play in reconstructing the radioactive contamination history of different glaciated regions of the Earth.